2017
DOI: 10.17235/reed.2017.5210/2017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of direct-acting antiviral therapy in patients with a HCV/HIV coinfection. A multicenter cohort study

Abstract: HCV treatment in coinfected patients is highly successful in terms of SVR rate in the real-life setting and toxicity is exceptional. We identified no specific predictors of an unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In this international cohort of PLWH coinfected with HCV treated with DAAs, we observed high rates of HCV cure (93% overall, including 91.4% of PLWH with cirrhosis) similar to other real-world HCV-coinfected cohorts [18–20] and despite the high prevalence of ongoing barriers to care in our cohort. Among the 7% of patients who failed therapy, patient-related factors prompting premature DAA discontinuation predominated over DAA virologic failure.…”
Section: Discussionsupporting
confidence: 85%
“…In this international cohort of PLWH coinfected with HCV treated with DAAs, we observed high rates of HCV cure (93% overall, including 91.4% of PLWH with cirrhosis) similar to other real-world HCV-coinfected cohorts [18–20] and despite the high prevalence of ongoing barriers to care in our cohort. Among the 7% of patients who failed therapy, patient-related factors prompting premature DAA discontinuation predominated over DAA virologic failure.…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study showed that a sustained viral response was achieved in greater than 95% of treated patients [ 7 ], and this result is consistent with our data. Toxicity and therapeutic abandonment were exceptional [ 20 ]. The COVID-19 pandemic is one of the main factors that explains the decrease in the number of cases treated in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent HCV genotypes associated with parenteral drug use in Europe are GT1a and GT3a. GT1a dominates in Spain among people who inject drugs 53 , 54 and HIV/HCV coinfected 7 , 55 . According to a recent observational analysis, from 1988 to 2015 in North-Eastern Spain there has been an increase in the prevalence of GT1a, GT3 and GT4 associated with male gender and parental use of drugs, currently the most prevalent route of infection, and a concomitant decline of GT1b, associated with transfusion or parenteral/nosocomial transmission 56 .…”
Section: Discussionmentioning
confidence: 99%